Stereotypes, prejudice and discrimination of men in female-dominated professions and their views of masculinity. - Copias, Elvin B.; Tolentino, Sarah Sophia (2014.)
The study examined the possible stereotypes, prejudice and discriminations experienced by men in female-dominated jobs and its possible implication on their views of masculinity. Thirty (30) male professionals were asked to answer the BSRI and underwent an in-depth interview. Interview responses revealed that these men experience minimal amount of stereotype, prejudice and discrimination in the work place. BSRI results yielded most of the participants to have feminine and androgynous traits. They attributed the results on the fact that their chosen career requires several female characteristics (e.g. approchable, caring and welcoming). The participants described themselves as "redefined masculines".
Research Project (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Men, discrimination